A Study on Phase and Microstructure of Reduced Graphene Oxide Prepared by Heating Corncobs - Kusuma Wardhani Mas'udah; Ahmad Taufiq; Sunaryono Sunaryono (JPSE (Journal of Physical Science and Engineering), 2020)
The purpose of this study was to find out reduced graphene oxide (RGO) phases by identifying the system, elemental system, and microstructure of corncobs. Characterization was carried out by XRD and SEM-EDX spectroscopy. The temperatures used in this work are 100, 200, and 250 ºC with a holding time of 1 hour. XRD analysis shows that the RGO phase is formed by the structure of the aromatic layer arrangement (graphite 002), and the widening comes from small-dimensional crystallites perpendicular to the aromatic layer (graphite 120). The elements contained in the three samples have a dominant proportion in the elements carbon and oxygen. From the SEM results obtained the morphology of corncobs powder that looks like sheets. The reduced graphene oxide phase is formed from the process of reducing corncobs powder.DOI: http://dx.doi.org/10.17977/um024v5i22020p066